The Private Life of Merge Conflicts - Cunha, Marcela; Accioly, Paola; Borba, Paulo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
Collaborative development is an essential practice for the success of most nontrivial software projects. However, merge conflicts might occur when a developer integrates, through a remote shared repository, their changes with the changes from other developers. Such conflicts may impair developers’ productivity and introduce unexpected defects. Previous empirical studies have analyzed such conflict characteristics and proposed different approaches to avoid or resolve them. However, these studies are limited to the analysis of code shared in public repositories. This way they ignore local (developer private) repository actions and, consequently, code integration scenarios that are often omitted from the history of remote shared repositories due to the use of commands such as git rebase, which rewrite Git commit history. These studies might then be examining only part of the actual code integration scenarios and conflicts. To assess that, in this paper we aim to shed light on this issue by bringing evidence from an empirical study that analyzes git command history data extracted from the local repositories of a number of developers. This way we can access hidden integration scenarios that cannot be accessed by analyzing public repository data as in GitHub based studies. We analyze 95 git reflog files from 61 different developers. Our results indicate that hidden code integration scenarios are more frequent than the visible ones. We also find higher conflict rates than previous studies. Our evidence suggests that studies that consider only remote shared repositories might loose integration conflict data by not considering the developer’s local repository actions.